F(x)=3x^2 - 2x +1
f(-1)=3(-1)^2-2(-1)+1
f(-1)=3( 1 ) +2+1
f(-1)=3+3
f(-1)=6
Solve for c :
x⁴ + cx² + 100 = 0
cx² = -(x⁴ + 100)
c = - (x⁴ + 100)/x²
If x = 0, the right side is undefined and c would have no solution.
Answer:
C = 600 + 50s
Step-by-step explanation:
The students are planning to visits the Canada's wonderland. The students will spend a full day at the park.
The entry fee for each student is $50 and the bus cost is $600. Each student will pay $50 for entry into the park.
Let
the number of student = s
cost of the trip = C
Relating the variable C and s
The total amount of money the student will pay for entry fee = 50 × s = 50s
Therefore, cost of the trip can be expressed as follows
C = 600 + 50s
Answer:
h=3.24
Step-by-step explanation: